HUBUNGAN MINAT BELAJAR DAN RASA PERCAYA DIRI DENGAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Yenita, Roza (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2018)
This study aims to determine: (1) the relationship between interest in learning with learning outcomes civic education; (2) the relationship between self-confidence by learning outcomes civic education; and (3) the relationship between learning and confidence together with the civic education learning outcomes. Collecting data using test instrument and non-test. Before the instrument used in the study, first piloted in two equivalent classes  in vocational Dewantara defines as a trial class. Then tested the validity and reliability for each instrument. In the test instrument, test the validity of using Point biserial correlation and reliability testing using the Kuder-Richardson 20. While the validity of the test non-tes instrument using Product Moment correlation and reliability testing using Cronbach Alpha. The result of the research show that 23,8% of civic education leraning outcomes can be influenced jointly by the variable interest in learning and confidence and 76,2% are influenced by other factors beyond the variables X1 and X2.